Radar imaging complex with SAR and ASR for aerospace vechicle - Pavlikov, Volodimir; Belousov, Konstantin; Zhyla, Simeon; Tserne, Eduard; Shmatko, Olexandr; Sobkolov, Anton; Vlasenko, Dmytro; Kosharskyi, Volodimir; Odokiienko, Olexiy; Ruzhentsev, Mykola (Radìoelektronnì ì komp'ûternì sistemi (Online), 2021)
The subject of study in the article is the algorithms for radio monitoring of the Earth in a wide field of view from aerospace transport. The goal is to design a structural diagram of a radio complex that can operate simultaneously in two modes: modified synthetic aperture (SAR) and aperture synthesis (ASR), in accordance with algorithms synthesized by the maximum likelihood method. The modified SAR mode allows obtaining high-resolution radio images in the observation angle range ±(20°...50°) from the direction to the nadir. A method of combining a modified SAR algorithm is used, which differs from the classical imaging algorithm by the possibility of obtaining a higher spatial resolution, the payment for this is the complication of the signal processing algorithm associated with the implementation of decorrelating filters that expand the spectrum of received signals in each receiving path, and the ASR mode, which allows imaging using passive or active radar principles. The passive ASR mode provides for the imaging in the observation angle range of ±20° from the nadir based on the results of processing signals of its own broadband radio-thermal radiation, and the active mode – in the same observation angle range, but using the broadband noise signal of the backlight. An important result in the formation of a radio image in the specified viewing area when using the active mode of the ASR is that the images are close in physical content, namely, proportional to the specific effective reflection surface of the underlying surface. In addition, a distinctive feature of the synthesized algorithms is the use of wideband probing signals and, accordingly, the same input paths of receivers, which makes it possible to increase the signal-to-noise ratio of the output effect. Conclusions. The scientific novelty of the results obtained is as follows: a structural diagram of the radio complex was developed on the basis of algorithms synthesized by the maximum likelihood method. For the formation of a radio image in the radio complex, a combination of SAR and ASR (with two modes of operation) is implemented. This implementation is important, since it allows obtaining high-resolution images in the observation angle range of ±50° from the direction to the nadir. It is advisable to place the complex on airplanes, helicopters and spacecraft (preferably those that move in low orbits).